(untitled) (Medico Legal Update, 2021)
Background: Coronary artery bypass grafting (CABG) is one of the most common interventional procedures used worldwide to treat coronary artery disease. Despite patient expectations of the immediate benefits of CABG, some symptoms persist for weeks after hospital discharge, compromising the ability to return to a pre-surgery functional status. Objective: the study aims to evaluate the effect of educational guidelines on lifestyle modification and clinical outcomes for patients undergoing coronary artery bypass grafting’ surgery. Method: A quasi-experimental design was utilized for the study. A purposive sample of 60 patients undergoing coronary artery bypass grafting’ surgery. Results: There were highly statistically significant differences between the control and the study group subjects regarding a satisfactory level of total knowledge post implementation the educational guidelines at P value < 0.001,while there were highly statistically differences between the control and the study group subjects regarding the lifestyle behaviors post implementation of the educational guidelines at P< 0.001. Moreover there were statistically significant difference regarding total outcomes among control and study group subjects post educational guidelines. Conclusion: Implementation of the educational guidelines has highly significant positive effect on lifestyle modification and clinical outcomes for the studied patients undergoing CABG surgery